Encapsulation of coriander essential oil in cyclodextrin nanosponges: A new strategy to promote its use in controlled-release active packaging. (August 2019) - Silva, Filomena; Caldera, Fabrizio; Trotta, Francesco; Nerín, Cristina; Domingues, Fernanda C.
Abstract: In this work, we exploit the antimicrobial properties of coriander essential oil (CEO) incorporated in dextrin-derived nanosponges to create a stable controlled release system. Nanosponges (CD-NS) were loaded with CEO, characterized by means of scanning and transmission electron microscopy (SEM and TEM) and X-ray diffraction (XRD), and tested for their antimicrobial activity against foodborne pathogens. A head-space-solid phase microextraction coupled to gas chromatography (HS-SPME-GC–MS) method to assess CEO five major compounds was successfully validated. CEO loading was dependent on solvent and CD-NS choice. Additionally, CEO incorporation in CD-NS increased its crystallinity. While β-CD-NS and HP-β-CD:β-CD-NS incorporated higher CEO amounts than α-NS, the later proved more effective regarding their antimicrobial activity. CEO-α-CD-NS and CEO-HP-β-CD:β-CD-NS revealed a predominant bactericidal activity, CEO-β-CD-NS only exhibited a bacteriostatic action. We describe, for the first time, the incorporation of whole EOs in CD-NS and their ability to provide a controlled oil release, especially in the cases of β-derived-CD-NS, while inhibiting bacterial growth, creating a potential new strategy to overcome the poor efficacy of current antimicrobial food packaging. Industrial relevance: The manufacturing of antimicrobial food packages is still hindered by the problems posed by its lack of efficiency and poor compound stability. The fact that the cyclodextrin nanosponges synthetized in this work can provide a controlled release of antimicrobial active agent, in this case, coriander essential oil while preserving this compound's antimicrobial activity against foodborne pathogens can open the doors for its use in antimicrobial food packaging films. Furthermore, given that cyclodextrin nanosponges are stable at temperatures over 200 °C, gives the packaging industry the opportunity of incorporating this technology during the extrusion process of film making, making the process of active packaging materials cheaper, faster and more readily scalable. Highlights: HP-β: β-CD-NS encapsulated the highest amount of CEO (60 μg/mg NS). A HS-SPME-GC/MS method was validated to quantify CEO five major compounds. NS yielded a controlled CEO release dependent on culture medium and temperature. α-NS and HP-β: β-CD had a predominant bactericidal action on foodborne bacteria. NS-released CEO was effective at concentrations lower than the MIC for free CEO.